An architect’s relation to structure: Analysis of Pinki Cultural Sports Center by Ivan Antić - Petrović Milica; Skansi Luka (Spatium, 2018)
Architecture represents the synthesis of form, function and construction. In the works of the architect Ivan Antić this can be read at the first view of the building. A master in designing movement through an object, Antić constantly developed the relationship between function and form, as well as between function and construction. A detailed analysis of his work, projects and drawings, gives insight to these relations, making them clear. The observer can see the architect’s logic and simplicity in designing even the most complex buildings. The relationship between the design concept and the way the structure manifests itself in his projects will be presented in this paper. The logic behind the design of Pinki Cultural Sports Center, with emphasis on structure, as well as the relationship between the architect and the engineer can be seen throughout this paper. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR 36035: Spatial, Environmental, Energy and Social Aspects of Developing Settlements and Climate Change - Mutual Impacts]